Blood-Conservation Strategies in a Blood-Refusal Parturient with Placenta Previa and Placenta Percreta. Issue 5 (1st March 2016) - Mauritz, Amy A.; Dominguez, Jennifer E.; Guinn, Nicole R.; Gilner, Jennifer; Habib, Ashraf S.
Abstract : Abnormal placentation can be associated with significant blood loss and massive blood transfusions. Caring for parturients with abnormal placentation who refuse blood transfusion is very challenging. We present a 35-year-old, gravida 3, para 1, Jehovah's Witness at 35 weeks of gestation with placenta percreta, who underwent cesarean delivery and delayed hysterectomy. A multidisciplinary team developed a plan, including the use of perioperative erythropoietin and IV iron dextran, intraoperative acute normovolemic hemodilution, cell salvage, tranexamic acid, and uterine artery embolization. This strategy was successful in avoiding the need for allogeneic transfusion and ensuring an uneventful recovery after both surgical procedures.